2016
DOI: 10.21037/tlcr.2016.07.09
|View full text |Cite
|
Sign up to set email alerts
|

From diagnosis to therapy in lung cancer: management of CT detected pulmonary nodules, a summary of the 2015 Chinese-German Lung Cancer Expert Panel

Abstract: Improved risk classification criteria and novel imaging approaches for screening populations are highly required as more than half of lung cancer cases are false positive during the initial screening round if the National Lung Screening Trial (NLST) demographic criteria [≥30 pack years (PY) of cigarettes, age ≥55 years] are applied. Moreover, if the NLST criteria are applied to the Chinese population a high number of lung cancer patients are not diagnosed due to non-smoking related risk factors in China. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Low‐dose CT (LDCT) is recommended for routine screening and follow‐up of lung cancer in high‐risk populations because of its many advantages, including the high rate of detecting small lesions, elimination of overlapping structures, high resolution, low radiation dose, noninvasiveness, and inexpensiveness . The US National Lung Screening Trial confirmed 20% reduction in lung cancer‐related mortality in selected high‐risk populations, when screened by LDCT, despite poor specificity, over‐diagnosis, bias, and cost‐effectiveness concerns . Many people may be concerned about the radiation dose of CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐dose CT (LDCT) is recommended for routine screening and follow‐up of lung cancer in high‐risk populations because of its many advantages, including the high rate of detecting small lesions, elimination of overlapping structures, high resolution, low radiation dose, noninvasiveness, and inexpensiveness . The US National Lung Screening Trial confirmed 20% reduction in lung cancer‐related mortality in selected high‐risk populations, when screened by LDCT, despite poor specificity, over‐diagnosis, bias, and cost‐effectiveness concerns . Many people may be concerned about the radiation dose of CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…When the malignance of the nodule is confirmed or highly suspected, surgery is recommended depending on number of the nodules and the fitness of the individual. Lobectomy or anatomical segmentectomy is the treatment of choice (2).…”
Section: Therapymentioning
confidence: 99%
“…With the development of computed tomography (CT) technology, the clinical detection rate of small pulmonary nodules (SPNs) is increasing. SPNs are principally peripheral solitary or multiple small (5–10 mm in diameter) lesions present in the lungs, without atelectasis, hilar lymph node enlargement, or pleural effusion 1 , 2 . Their probability of malignancy is 3.3–10.8% 3 , 4 , and surgical treatment is accepted as the first choice in clinical practice.…”
Section: Introductionmentioning
confidence: 99%